Testing the accuracy of a new histomorphometric method for age-at-death estimation. (March 2019) - Lagacé, Frédérique; Verna, Emeline; Adalian, Pascal; Baccino, Eric; Martrille, Laurent
Highlights: The circularity of the osteons seems to be a difficult variable to reproduce with reliable results. Using Goliath et al.'s formula to estimate age in our sample did not provided accurate results. In light of these findings, the usefulness of this method in forensic context may be questioned. Abstract: Histomorphometric methods for age-at-death estimation constitute alternatives to macroscopic ones in the forensic context. However, all new methods must be tested on independent samples to justify their use and assure their accuracy. The main goal of this study was to test a new age-at-death method presented by Goliath et al. (2016) on a sample of 29 decalcified femur sections from individuals autopsied in the Institute of Legal Medicine of Montpellier, France. The formula proposed by the authors was not efficient to estimate the age-at-death in our sample, with only four out of 29 individuals well estimated. Despite this result, the same relationship between age and histomorphometric criteria was found, though at a lower intensity than what Goliath et al. previously found in their study. The use of a different bone preparation technique from Goliath et al. does not allow us to propose a definitive conclusion on the accuracy of this method.